Quality Assurance of Spirometry in a Population-Based Study –Predictors of Good Outcome in Spirometry Testing. (1st April 2014) - Tan, Wan C.; Bourbeau, Jean; O'Donnell, Denis; Aaron, Shawn; Maltais, Francois; Marciniuk, Darcy; Hernandez, Paul; Cowie, Robert; Chapman, Kenneth; Sonia Buist, A.; Sin, Don; Mark Fitzgerald, J.; et al.
Abstract: Background: The assurance of high-quality spirometry testing remains a challenge. Methods: Spirometry training consisted of standardized coaching followed by certification for 35 spirometry-naïve and 9 spirometry-experienced research assistants. Spirometry was performed before and after bronchodilator (BD) in random population samples of 5176 people aged 40 years and older from 9 sites in Canada. using the hand-held EasyOne spirometer (ndd Medical Technologies Inc., Andover, MA, USA). Pulmonary function quality assurance with over reading was conducted centrally in Vancouver: spirograms were reviewed and graded according to ATS/ERS standards with prompt feedback to the technician at each site. Descriptive statistics were calculated for manoeuvre acceptability and repeatability variables. A logistic regression model was constructed for the predictors of spirometry quality success. Results: 95% of test sessions achieved pre-determined quality standards for back extrapolated volume (BEV), time to peak flow (PEFT) and end of test volume (EOTV). The mean forced expiratory time (FET) was 11.2 seconds. Then, 90% and 95% of all manoeuvres had FEV1 and FVC that were repeatable within 150 ml and 200 ml respectively. Test quality was slightly better for post-BD test sessions compared with pre-BD for both groups of research assistants. Independent predictors of acceptable test quality included participant characteristics: female sex, younger age, greater BD responsiveness; but not study site or prior experience in completing spirometry by the technologist. Conclusions: Good quality spirometry tests are attainable in large multicenter epidemiological studies by trained research assistants, irrespective of their prior experience in spirometry.